Pengaruh Kualitas Pelatihan Terhadap Kinerja Penyidik di Ditreskrimum Polda Lampung dengan Kompetensi Sebagai Variabel Mediasi - Kartini Aprilia; Agus Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of training quality on the performance of investigators at the Directorate of General Criminal Investigation (Ditreskrimum) of the Lampung Regional Police, with competency as a mediating variable. The study is motivated by the need to enhance investigator professionalism in response to the increasing complexity of criminal cases and rapid technological developments. This research employs a quantitative approach with a causal research design. The population consists of all 54 investigators at Ditreskrimum Polda Lampung, who were included as the sample using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that training quality has a positive and significant effect on investigator competency and performance. Competency also has a positive and significant effect on investigator performance. Furthermore, competency is proven to significantly mediate the effect of training quality on investigator performance.